The influence of maternal factors and residential building characteristics on infant mortality in Papua Province, Indonesia, based on secondary data analysis of the IDHS 2017 - Putri, Septinda Ayu Prasninda Januar; Handayani, Samsriyaningsih; Ningrum, Astika Gita (Universitas Airlangga, 2025)
HIGHLIGHTS This study focused on Papua, which had the highest infant mortality rate, using a multivariate approach to analyze various factors. Data from the IDHS 2017 and robust statistical analysis were expected to aid in formulating effective health policies. The uniqueness of this research lies in its broader scope of variables, including education and employment, while considering the social and cultural context of Papua, providing new insights into infant health issues. ABSTRACT Objective: Infant mortality remains a critical global public health concern, with 2.4 million neonates dying within the first month of life in 2020. In Indonesia, the infant mortality rate stood at 16.85 per 1,000 live births in 2022, with Papua Province reporting the highest incidence. This study seeks to examine the determinants of infant mortality in Indonesia, with a focus on maternal age, antenatal care, immunization status, delivery conditions, parity, educational attainment, maternal employment, household income, and housing characteristics. Materials and Methods: This study utilized a quantitative cross-sectional design, analyzing secondary data from the Indonesian Demographic and Health Survey (IDHS) 2017. The sample comprised 658 women aged 15–49 years who delivered infants aged 0–11 months between 2012 and 2017 in Papua Province. The analytical approach consisted of three phases: univariate analysis to assess frequency distributions, bivariate analysis employing logistic regression (p < 0.05) to examine associations, and multivariate analysis using multiple logistic regression for simultaneous variable assessment. Variables with p-values < 0.25 were retained, while those exceeding 0.05 were sequentially eliminated, with emphasis on Odds Ratio (OR) variations. Results: The analysis identified maternal education level as the most significant predictor of infant mortality, demonstrating an Adjusted Odds Ratio (AOR) of 43.579 (p-value = 0.000, 95% CI = 5.549–342.235). Mothers with only basic education were 43.57 times more likely to experience infant mortality compared to those with advanced education. Conclusions: Maternal socioeconomic factors exert a substantial influence on infant mortality in Papua Province, and these findings can guide targeted interventions to mitigate mortality rates in the region.